A Culturally Adapted Smoking Cessation App (IndigeQuit) for American Indian and Alaska Native Adults: Protocol for a Randomized Clinical Trial - Jonathan B Bricker; Margarita Santiago-Torres; Brianna M Sullivan; Kristin E Mull; Hershel W Clark; Chase Kornacki; Trivia Afraid of Lightning-Craddock; Dean S Seneca; Crystal M Stanford; Sierra L Wilcox; Patricia Nez Henderson; Lonnie Nelson (JMIR Research Protocols, 2026)
Background Due to limited access to evidence-based cessation support, American Indian and Alaska Native (AI/AN) adults are half as likely to quit commercial cigarette smoking as other racial and ethnic groups. Geographical barriers, underfunded health systems, and limited integration of cessation services into routine care have reduced access to effective treatment in AI/AN communities. These challenges are compounded by a lack of culturally relevant interventions tailored to AI/AN adults. Thus, there is an urgent need for accessible, scalable, and culturally relevant interventions. Objective Here, we describe the protocol for a randomized clinical trial (RCT) testing the efficacy of a culturally adapted smoking cessation app (IndigeQuit) developed specifically to help AI/AN adults quit smoking commercial cigarettes compared to a standard, nontailored app (QuitGuide). Methods To improve the relevance and acceptability of cessation support to AI/AN adults, IndigeQuit was developed through a cultural adaptation of iCanQuit, an evidence-based smartphone app grounded in acceptance and commitment therapy that teaches skills for accepting cravings to smoke. The cultural adaptation used a user-centered, community-based participatory research mixed methods approach in collaboration with a community advisory board (CAB) comprising AI/AN individuals. Cultural adaptations included the use of Native imagery; stories featuring AI/AN adults and elders emphasizing culture, spirituality, family, and community; and the important distinction between ceremonial and commercial tobacco. A total of 776 AI/AN adults who smoke and want to quit are being recruited nationwide and randomized to receive IndigeQuit or QuitGuide for 12 months. The primary aim of the RCT is to determine the efficacy of IndigeQuit compared with QuitGuide for 30-day abstinence at 12 months. Secondary aims include abstinence at earlier time points, identifying mediators and moderators of treatment effects, and assessing engagement and satisfaction. Qualitative interviews with IndigeQuit participants and CAB members will inform the development of a subsequent guide to support the broad dissemination of IndigeQuit nationwide. Results The National Cancer Institute funded this study in 2024 (grant R01 CA284687), with the grant awarded to the principal investigator, JBB. As of August 2026, a total of 590 AI/AN adults had been enrolled in the trial. Data collection started in July 2025 and is expected to be completed by November 2028. Conclusions The IndigeQuit app was designed to deliver evidence-based smoking cessation treatment that is culturally adapted to AI/AN communities and grounded in acceptance and commitment therapy. If effective, this intervention could offer a more scalable and culturally relevant treatment to AI/AN communities nationwide, helping to reduce smoking-related health inequities. Trial Registration ClinicalTrials.gov NCT06145763; https://clinicaltrials.gov/study/NCT06145763 International Registered Report Identifier (IRRID) DERR1-10.2196/102675